Pemanfaatan Instrumen EPDS untuk Mengetahui Kejadian Baby Blues Syndrome Berdasarkan Kondisi Sosial dan Demografi di Indonesia - Pratiwi, Kurniasari (Jurnal Kesehatan, 2023)
The period of pregnancy, childbirth and postpartum are unforgettable moments that are both happy and full of challenges for women. In this process, women will experience significant psychological and physical changes, so they need to prepare themselves. Unprepared women can experience various psychological disorders. Nearly 70% of mothers experience sadness or baby blues/postpartum blues syndrome. With the right coping strategy and a good support system, baby blues syndrome can be overcome without professional help, but data proves cases that are left untreated can escalate into more severe depression and can be fatal for the mother and baby. The aim of the research is to analyze the relationship between baby blues syndrome based on demographic factors in Indonesia. The research method used is descriptive quantitative, and data analysis uses Chi square. Assessment of the incidence of postpartum blues using the Edinburgh Postnatal Depression Scale (EPDS). Results: Based on data analysis using the cross-sectional method on 379 respondents, it was found that as many as 35% had postpartum blues or baby blues syndrome, 23% experienced severe conditions or postpartum depression and 42% did not experience (normal). Based on bivariate data analysis, there was no significant relationship between parity and ethnicity with the incidence of baby blues syndrome. In addition, there is a relationship between the presence of postpartum caregivers with the incidence of baby blues syndrome.